A narrative review of online food delivery in Australia: challenges and opportunities for public health nutrition policy. Issue 1 (9th January 2023) - Bates, Sarah; Reeve, Belinda; Trevena, Helen
Abstract: Objective: Online food delivery (OFD) platforms offer consumers a convenient and fast delivery service of foods and drinks sourced from foodservice partners (e.g. restaurants, quick service restaurants). There is a need to assess the impact of this emergent segment of the foodservice sector on diet and diet-related health. The aim of this narrative review was to describe the OFD sector in Australia, its use and identify potential ways to include OFD platforms in existing public health nutrition policy. Design: A search was conducted in peer-reviewed and grey literature. Sources were analysed and synthesised to report the characteristics of OFD platforms, delivery process, users and potential drivers of usage. The aim and scope of public health nutrition policies were analysed to identify ways of including OFD platforms. Setting: Australia. Participants: General population. Results: There are three main operators with 9000–16 000 foodservice partners based predominantly in the main cities of Australia. OFD revenue has grown by 72 % in the last 5 years and is predicted to increase driven by usage by working adults with high disposable income who demand convenience. Current policies and initiatives aimed at manufacturers, retailers and foodservice outlets do not specifically regulate OFD platforms, although there is scope for these to be extended to such platforms. Conclusions: OFD platforms are disruptors of the foodservice sector. Innovative and consistent health policy options that target the unique challenges and opportunities posed by OFD platforms are required to limit the potentially negative impact of OFD platforms on diet and diet-related health.